Equilibria and dislocations in epitaxial growth. (May 2017) - Fonseca, I.; Leoni, G.; Morini, M.
Abstract: An overview of recent analytical developments in epitaxial growth is presented. The energy release via the onset of dislocations is addressed. Regularity of quasistatic equilibria is studied both in the absence and in the presence of dislocations. Morphological evolution of anisotropic epitaxially strained films is considered under the assumption that the surface evolves by surface diffusion under the influence of a chemical potential.